Anti‐Swelling, Robust, and Adhesive Extracellular Matrix‐Mimicking Hydrogel Used as Intraoral Dressing. Issue 20 (14th April 2022) - Wu, Jing; Pan, Zhao; Zhao, Zheng‐Yi; Wang, Mo‐Han; Dong, Liang; Gao, Huai‐Ling; Liu, Chong‐Yuan; Zhou, Pu; Chen, Lu; Shi, Chao‐Ji; Zhang, Zhi‐Yuan; Yang, Chi; et al.
Abstract: Due to the wet and dynamic environment of the oral cavity, the healing of intraoral wounds, such as tooth extraction wounds, requires stable and firm wound dressings. In clinical practice, cotton balls and gauze s, sponge plugs, or sutures are used to treat extraction wounds, but none of these means can continuously isolate the wound from the intraoral environment and facilitate ideal healing conditions. Herein, inspired by the natural extracellular matrix, a family of wound dressings is developed for intraoral wound repair. Infiltrating a ductile long‐chain hydrogel network into a prefabricated, sturdy macromolecular meshwork and in situ crosslinking endowed the composite hydrogel with controllable swelling behaviors and robust mechanical properties. The macromolecular meshwork functioned as the backbone to support the composite and restricts the swelling of the long‐chain hydrogel network. In vitro tests verified that this wound dressing can provide durable protection for intraoral wounds against complex irritations. Furthermore, accelerated wound healing occurred when the wound dressing is applied in vivo on a canine tooth extraction model, due to the effective reduction of acute inflammation. These results suggest that this family of bioinspired hydrogels has great potential for application as intraoral wound dressing. Abstract : An extracellular matrix‐mimicking hydrogel wound dressing is designed as tooth extraction adhesive wound dressing for intraoral application. The hydrogel exhibits excellent anti‐swelling efficiency, along with consistent mechanical and adhesive robustness in aqueous environments. In vitro and in vivo tooth extraction models demonstrate the stability of hydrogels as physical and antibacterial barriers for intraoral wounds, leading to continuous protection and effective healing acceleration.